Recent advances in oridonin derivatives with anticancer activity - Sobral, Pedro J. M.; Vicente, André T. S.; Salvador, Jorge A. R. (Frontiers in Chemistry, 2023)
Cancer is a leading cause of mortality worldwide, and its incidence is rapidly growing over the years. In 2020, there were an estimated 10 million cancer deaths and 19.3 million new cases around the globe. Population growth and aging, and high systemic toxicity and chemoresistance associated with conventional anticancer therapies, are responsible factors that reflect this increase in cancer incidence and mortality. And so, efforts have been made to search for novel anticancer drugs with fewer side effects and greater safety and therapeutic effectiveness. Nature continues to be the main source of biologically active lead compounds, and diterpenoids are considered one of the most important families since many have been reported to possess anticancer properties. Oridonin is an ent-kaurane tetracyclic diterpenoid isolated from Rabdosia rubescens, which has been the target of extensive research over the last years. It displays a broad range of biological effects including neuroprotective, anti-inflammatory, and anticancer activity against a variety of tumor cells. Several structural modifications on the oridonin and biological evaluation of its derivatives have been performed, creating a library of compounds with improved pharmacological activities. This mini-review aims to highlight the recent advances in oridonin derivatives as potential anticancer drugs, while succinctly exploring their proposed mechanisms of action. To wind up, future research perspectives in this field are also disclosed.